Population Viability of Sea Turtles in the Context of Global Warming - MAURER, ANDREW S.; SEMINOFF, JEFFREY A.; LAYMAN, CRAIG A.; STAPLETON, SETH P.; GODFREY, MATTHEW H.; REISKIND, MARTHA O. BURFORD (Bioscience, 2021)
Sea turtles present a model for the potential impacts of climate change on imperiled species, with projected warming generating concern about their persistence. Various sea turtle life-history traits are affected by temperature; most strikingly, warmer egg incubation temperatures cause female-biased sex ratios and higher embryo mortality. Predictions of sea turtle resilience to climate change are often focused on how resulting male limitation or reduced offspring production may affect populations. In the present article, by reviewing research on sea turtles, we provide an overview of how temperature impacts on incubating eggs may cascade through life history to ultimately affect population viability. We explore how sex-specific patterns in survival and breeding periodicity determine the differences among offspring, adult, and operational sex ratios. We then discuss the implications of skewed sex ratios for male-limited reproduction, consider the negative correlation between sex ratio skew and genetic diversity, and examine consequences for adaptive potential. Our synthesis underscores the importance of considering the effects of climate throughout the life history of any species. Lethal effects (e.g., embryo mortality) are relatively direct impacts, but sublethal effects at immature life-history stages may not alter population growth rates until cohorts reach reproductive maturity. This leaves a lag during which some species transition through several stages subject to distinct biological circumstances and climate impacts. These perspectives will help managers conceptualize the drivers of emergent population dynamics and identify existing knowledge gaps under different scenarios of predicted environmental change.